A bug's life - Lasseter, John (Pasig City : ViVa Video, 1999)
Journey inside the miniature world of bugs for bigger-than-life fun and adventure under every leaf. Crawling with imaginative characters, hilarious laughs and colorful, innovative computer animation, Disney and Pixar's A Bug's Life will delight everyone in your family! On behalf of "oppressed bugs everywhere", an inventive ant named Flik hires "warrior bugs" to defend his colony from a horde of freeloading grasshoppers, led by Hopper. But when Flik's calvary turns out to be a misfit group of circus performers, the stage is set for comic confusion...as well as unlikely heroes! Featuring a star-studded voice cast, A Bug's Life presents as amazing new perspective on teamwork and determination -- revealing subtle new details each time you watch it!